Pendampingan Kegiatan Aksi Beberasih Pada Musala Oleh Siswa Hijaz SMAN 2 Palangka Raya - Priolawati, Melly; Surawan, Surawan; Susmiati, Susmiati (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Cleanliness is an important aspect of religious life, especially in Islam, where cleanliness is considered part of the faith. The community service activity "Aksi Beberasih" carried out by Hijaz students at SMAN 2 Palangka Raya aims to increase awareness of the importance of maintaining cleanliness in worship environments, especially prayer rooms. The method used during the implementation of this community service activity is a service learning approach, including physical cleaning of prayer rooms, organizing cleaning tools, and educating students about the values ​​of cleanliness. The results of this activity show a significant increase in the cleanliness and comfort of prayer rooms, as well as strengthening students' awareness of the responsibility to maintain the cleanliness of places of worship. This activity also succeeded in establishing good cooperation between students and is hoped to become a model for sustainable service activities in the future.